Komunikasi Persuasif Digital BAPENDA Lombok Timur melalui Instagram dalam Mendorong Kepatuhan Pajak Bumi dan Bangunan: Analisis Engagement Instagram @bapendalotim - Ziat Wijaya; Iwan Joko Prasetyo; Redi Panuju (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the digital persuasive communication conducted by BAPENDA Lombok Timur through Instagram in encouraging Land and Building Tax compliance. The analysis was conducted using a quantitative descriptive approach based on Socialinsider analytical data for 30 days. Indicators used include the number of followers, engagement rate, total posts, total engagements, and total organic views. In addition, this study examined the three posts with the highest engagement rate to see the most effective content patterns. The results showed that the @bapendalotim account had 265 followers, an engagement rate of 1.74%, a total of 10 posts, total engagements of 46, and total Organic Views of 826. The top three posts recorded engagement rates of 3.396%, 1.887%, and 1.509%. Exploratory, the average engagement rate of the top three posts reached 2.264%, higher than the average of the other seven posts which inferentially was around 1.515%. An exploratory correlation test between top post category and engagement yielded a coefficient of r = 0.609, while a simple regression showed that top post status was associated with an increase in engagement of approximately 0.749 percentage points. These findings suggest that featured content can generate higher engagement, but performance across posts remains inconsistent.